Tenure challenges to implementing forest landscape restoration in northwestern Madagascar - McLain, Rebecca; Ranjatson, Patrick; Lawry, Steven; Rakotonirina, Jean Mananga; Randrianasolo, Renaud; Razafimbelo, Ny Tolotra (Center for International Forestry Research, 2019)
Madagascar has established ambitious goals for restoring its degraded forests under the Bonn Challenge; tenure rights and tenure security are likely to affect landholders willingness to invest in forest landscape restoration practices. In northwestern Madagascar (Boeny region), tenure challenges in three major local land categories (forests, savannas and seasonally flooded bottomlands) need to be considered; each category has particular tenure issues associated with it.